Effect of Intermittent Lighting System on Some of the Productive Performance of Laying Hens - Faten , Bahloul; Hashem, Y.; Abboud, M. (International Journal of Poultry Science, 2014)
The research was conducted at Krabo modern research poultry house of Agriculture Faculty, Damascus University during August, 2011 till October, 2012. A total of 1512 one-day-old chicks of Babcock B-300-hybrid layer hens distributed randomly and equally into six groups with 3 replicates in the same group were housed until the age of 17 weeks in a closed house with deep litter and then transferred to the production house equipped with batteries of a three-tries until the age of 60 weeks in order to determine the effect of intermittent lighting on some of productive performance of laying hens. Chicks in the first group, G1 (control 1) were exposed to step down of lighting through the stage of growth and step up through the production stage In G2 (control 2), chicks were exposed to short constant step up lighting system while chicks in G3, G4, G5 and G6 were exposed to intermittent lighting-step up, step down intermittent, short constant-intermittent and intermittent-intermittent of lighting systems, respectively. Results showed that the application of the lighting system in G5 had no significant effect on the averages of mortality rate and the live body weight but birds showed significant earlier sexual maturity and improvement in the production of egg per hen compared with those of G1. Results also showed a significant decrease in the average of egg weight compared with G1 but significant increase in the same index compared with G2. However, a significant increase in the average of egg mass produced per hen compared with those of G1.